META ANALYSIS THE EMISION OF GREEN PORT CITY : A LITERATURE REVIEW - Taufik Mulya Ibrahim; Denny Nurkertamanda; Hery Suliantoro (Journal of Industrial Engineering Management, 2023)
ABSTRAK Air emission not only from waste or gas from chimney of factory or ships in port, but also from leaking gas of freon/chloro in air that can damaging the ozone. Our current understanding of the sources and increase in emissions of leaked refrigerant gases derives from two data sources: ground-based and airborne point measurements, or from reports of the quantity of products manufactured and purchased. Thus, port-related air pollutant emissions and their environmental impacts are not systematically reported. The solution to the environmental impacts of refrigerant gases would therefore pass by a gas which contains no chlorine no fluorine and does not reject any CO2 emissions in the atmosphere, in brief a green gas. The method used is expected to be able to map the center of the pollutant source.